Using the Technical Teacher Application (Gl 4.0) in the Post Pandemic - Prayetno, Prayetno; iqbal, Muhammad; Jamaludin, Jamaludin; Pinem, Windawati (Green Publisher Indonesia, 2022)
The implementation of the e-learning teaching and learning process using commercial media still has limited access and some focuses on the knowledge aspect, so that it becomes an obstacle for teachers in assessing aspects of students' attitudes and character. This article aims to describe the development of a blended learning platform in order to develop students' readiness to use the internet as a learning mode in the era of internet-based technology openness. The research method used in this study is a qualitative research method with a case study approach. Through the object of research teachers and students. Obtaining data by observation, documentation study and focus group discussion were then analyzed by data reduction, data presentation and conclusion drawing. The results of this study indicate that there is user readiness in accessing the LMS platform through optimal use of GL 4.0, the establishment of teachers presenting KBM planning in virtual managerial has been achieved by being shown to be able to prepare and upload learning resources (teaching materials and enrichment materials), assessment of student achievement and interaction. and communication of teachers with students or students with colleagues. GL 4.0 provides a space for teacher creativity so that the learning space is facilitated properly and is fun for students. Teachers in the maturity of mixed learning management between online and offline (blended learning) are the main requirements to be able to carry out these learning activities . The conclusion is that GL 4.0 is the platform of choice for blended learning KBM adaptation in schools because the simplicity of the platform makes it easy for users to complete media attributes or features that facilitate the conditions for blended learning to take place.